Evaluating the Effects of Three High Intensity Interval Training Protocols on Maximum Oxygen Consumption and Leg Strength in Recreational Football Athletes - Wirat Sonchan; Saralee Sonchan; Ratanyoo Longrak (Physical Education Theory and Methodology)
Objectives. This study aimed to examine the effects of three high intensity interval training (HIIT) protocols on VO₂max and leg strength in recreational football athletes.